Velocity-Free MS/AE Source Location Method for Three-Dimensional Hole-Containing Structures. (July 2020) - Dong, Longjun; Hu, Qingchun; Tong, Xiaojie; Liu, Youfang
Abstract: Microseismic/acoustic emission (MS/AE) source localization method is crucial for predicting and controlling of potentially dangerous sources of complex structures. However, the locating errors induced by both the irregular structure and pre-measured velocity are poorly understood in existing methods. To meet the high-accuracy locating requirements in complex three-dimensional hole-containing structures, a velocity-free MS/AE source location method is developed in this paper. It avoids manual repetitive training by using equidistant grid points to search the path, which introduces A* search algorithm and uses grid points to accommodate complex structures with irregular holes. It also takes advantage of the velocity-free source location method. To verify the validity of the proposed method, lead-breaking tests were performed on a cubic concrete test specimen with a size of 10 cm × 10 cm × 10 cm. It was cut out into a cylindrical empty space with a size of ϕ 6 cm × 10 cm. Based on the arrivals, the classical Geiger method and the proposed method are used to locate lead-breaking sources. Results show that the locating error of the proposed method is 1.20 cm, which is less than 2.02 cm of the Geiger method. Hence, the proposed method can effectively locate sources in the complex three-dimensional structure with holes and achieve higher precision requirements.